Vapor linker exchange of partially amorphous metal–organic framework membranes for ultra‐selective gas separation. Issue 5 (18th January 2022) - Su, Pengcheng; Tang, Huiyu; Jia, Miaomiao; Lin, Yanshan; Li, Wanbin
Abstract: Metal–organic framework (MOF) membranes are promising for efficient separation applications. However, the uncontrollable pathways at atomic level impede the further development of these membranes for molecular separation. Herein we show that vapor linker exchange can induce partial amorphization of MOF membranes and then reduce their transport pathways for precisely molecular sieving. Through exchanging MOF linkers by incoming ones with similar topology but higher acidity, the resulted metal‐linker bonds with lower strength cause the transformation of MOF membranes from order to disorder/amorphous. The linker exchange and partial amorphization can narrow intrinsic apertures and conglutinate grain boundary/crack defects of membranes. Because of the formation of ultra‐microporous amorphous phase, the MOF composite membrane shows competitive H2 /CO2 selectivity up to 2400, which is about two orders of magnitude higher than that of conventional MOF membranes, accompanied by high H2 permeance of 13.4 × 10 −8 mol m −2 s −1 Pa −1 and good reproducibility and stability.